Modulating the JAK/STAT pathway with natural products: potential and challenges in cancer therapy - Bhagyalakshmi Nair; Anjana Menon; M. Rithwik Kalidas; Lekshmi R. Nath; Daniela Calina; Javad Sharifi-Rad (Discover Oncology)
Abstract The Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) pathway is a critical signaling network governing cellular functions such as immune responses, proliferation, and apoptosis. Dysregulation of this pathway is strongly implicated in cancer progression. This review explores the therapeutic potential of natural products, including Curcumin, Resveratrol, Apigenin, and Epigallocatechin Gallate (EGCG), as modulators of the JAK/STAT pathway. These phytochemicals exhibit anticancer activity by inhibiting JAK/STAT phosphorylation, blocking STAT dimerization, and interfering with STAT-DNA binding. A systematic evaluation of included peer-reviewed studies highlights their promise as complementary agents to conventional cancer therapies. However, challenges such as poor bioavailability and the need for robust clinical validation remain significant hurdles. Addressing these limitations through advanced drug delivery systems and rigorous trials could unlock their full potential in cancer treatment.